2015
DOI: 10.3171/2014.9.jns14233
|View full text |Cite
|
Sign up to set email alerts
|

Grade 2 meningioma and radiosurgery

Abstract: OBJECT World Health Organization Grade 2 meningiomas are aggressive tumors associated with a high recurrence rate leading to repeated surgical procedures, which can seriously worsen a patient's neurological status. Although radiosurgery is an increasingly popular technique, its role in the management of Grade 2 meningiomas has yet to be defined. In this study the authors aimed to evaluate radiosurgery in achieving control of proven tumor progression occurring after resection of Grade 2 meningioma. METHODS Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…[9][10][11]13,14 As salvage surgical interventions after tumor recurrence are accompanied by high morbidity and possible neurological dysfunction, many neuro-oncologists advocate for adjuvant early radiation therapy in patients with grade 2 meningiomas. 9 There have not been many studies analyzing histopathologically confirmed WHO grade 2 meningiomas with a large sample size of patients. To our knowledge, this is the biggest cohort of homogenous histopathologically confirmed grade 2 meningiomas treated with GK RS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[9][10][11]13,14 As salvage surgical interventions after tumor recurrence are accompanied by high morbidity and possible neurological dysfunction, many neuro-oncologists advocate for adjuvant early radiation therapy in patients with grade 2 meningiomas. 9 There have not been many studies analyzing histopathologically confirmed WHO grade 2 meningiomas with a large sample size of patients. To our knowledge, this is the biggest cohort of homogenous histopathologically confirmed grade 2 meningiomas treated with GK RS.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies utilized local-regional control as an end point, while a few others used OS. [9][10][11]13,14 Our study analyzed both the LC and OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiosurgery has been utilized for management of atypical meningiomas with encouraging outcomes [45][46][47][48][49][50][51] . Radiosurgery may be utilized for improved precision in RT delivery by use of stereotactic localization and optimized normal tissue sparing with steeper dose gradients around the target volume.…”
Section: Treatmentmentioning
confidence: 99%